Renal Denervation Attenuates Adverse Remodeling and Intramyocardial Inflammation in Acute Myocardial Infarction With Ischemia–Reperfusion Injury - Wang, Kun; Qi, Yu; Gu, Rong; Dai, Qing; Shan, Anqi; Li, Zhu; Gong, Chenyi; Chang, Lei; Hao, Han; Duan, Junfeng; Xu, Jiamin; Hu, Jiaxin; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Inhibition of sympathetic activity and renin-angiotensin system with renal denervation (RDN) was proved to be effective in managing refractory hypertension, and improving left ventricular performance in chronic heart failure. The inhibition of sustained sympathetic activation prevents or delays the development of cardiac fibrosis and dysfunction that occurs after myocardial infarction and ischemia-reperfusion injury. The translational efficiency of RDN remains to be defined in preclinical animal studies. Objectives This study investigated the therapeutic role of RDN in adverse remodeling and intramyocardial inflammation in myocardial ischemia-reperfusion (MI/R) injury. Methods Herein, fifteen minipigs were subjected to 90-min percutaneous occlusion of the left anterior descending artery followed by reperfusion. Eight animals received simultaneous RDN using catheter-based radiofrequency ablation (MI/R-RDN). Cardiac function and infarct volume were measured in vivo, followed by histological and biochemical analyses. Results The infarct volume in I/R-RDN pigs reduced at 30 days postreperfusion, compared to I/R-Sham animals. The levels of catecholamine and cytokines in the serum, kidney cortex, the border and infarcted regions of the heart were significantly reduced in I/R-RDN group. Moreover, the gene expression of collagen and the protein expression of adrenergic receptor beta 1 in heart were also decreased in I/R-RDN mice. Additionally, RDN therapy alleviated myocardial oxidative stress. Conclusions RDN is an effective therapeutic strategy for counteracting postreperfusion myocardial injury and dysfunction, and the application of RDN holds promising prospects in clinical practice.